EFFECTIVENESS OF PNF STRETCHING VERSUS STATIC STRETCHING ON PAIN AND HAMSTRING FLEXIBILITY FOLLOWING MOIST HEAT IN INDIVIDUALS WITH KNEE OSTEOARTHRITIS (International Journal of Physiotherapy, 2016)
Background: Osteoarthritis (OA) is a degenerative joint disease and one of the major public health problem that causesfunctional impairment and reduced quality of life. To compare the effectiveness of PNF Hold relax stretching versus Static stretching on pain and flexibility of hamstring following moist heat in individuals with knee osteoarthritis. Hamstring tightness is the major problem in knee osteoarthritis individuals. Therefore the need of study is comparing the effectiveness of PNF Hold relax stretching versus static stretching on pain and flexibility of hamstrings following moist heat in knee osteoarthritis participants. Determining the effects of PNF Hold relax stretching versus Static stretching along with moist heat on pain and hamstring flexibility by VAS and Active knee extension range of motion in knee osteoarthritis individuals.Methods: 30 subjects with symptoms of knee osteoarthritis were randomly distributed into 2 groups 15 in each group. PNF Hold relax stretching along with moist heat is compared to Static stretching along with moist heat. Pain was measured by Visual Analogue Scale (VAS) and hamstring flexibility by Active knee Extension Range of Motion (AKEROM) by universal goniometer. Measurements are taken pre and post intervention.Results: The results indicated PNF Hold relax stretching along with moist heat showed a statistically significant improvement in pain (p